Inheritance of juvenile traits and immune competence in Gramapriya male line chicken - PRASAD, ATHE RAJENDRA; GNANAPRAKASH, M; MAHENDER, M; SAGAR, N GOVARDHANA; RAJKUMAR, U (The Indian Journal of Animal Sciences, 2016)
High correlation estimates between body weight and shank length revealed strong association among traits. The significant positive association between 4 and 6 weeks shank length and body weight in the Gramapriya male line chicken suggest the breeder to pre-pone the selection to 4 weeks age which economizes the production cost. Besides, the immune competence of the birds was also found to be better, making them suitable male line for production of backyard poultry varieties.